2017
DOI: 10.1177/0003319717714918
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Neutrophil-Lymphocyte Ratio and In-Stent Restenosis in Patients With Femoropopliteal Chronic Total Occlusions

Abstract: We investigated the relationship between the neutrophil-lymphocyte ratio (NLR) and in-stent restenosis (ISR) in patients with femoropopliteal chronic total occlusions (CTOs). The study enrolled 180 patients who had undergone successful stenting treatment for femoropopliteal CTO. Patients with ISR were subsequently classified into 2 groups: early-ISR (within 1 year) and late-ISR (after 1 year). The clinical characteristics, angiographic data, and follow-up data were recorded. The baseline NLR was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…The neutrophil-lymphocyte ratio (NLR) has been shown to be a marker of inflammation and closely related to increased cardiovascular mortality and morbidity [6,7]. Although the relationship between various inflammatory biomarkers, including NLR, and the occurrence of ISR has been investigated [8][9][10]. No studies have evaluated the effectiveness of the NLR value after (NLR after ), NLR change(NLR change ), defined as the NLR value before (NLR before ) and after (NLR after ) superficial femoral artery stenting (SFAS) intervention and NLR change ratio (NLR ratio ), defined as the ratio of NLR change to NLR before, in prediction of ISR in superficial femoral artery stents, which are at high risk for the occurrence of ISR.…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil-lymphocyte ratio (NLR) has been shown to be a marker of inflammation and closely related to increased cardiovascular mortality and morbidity [6,7]. Although the relationship between various inflammatory biomarkers, including NLR, and the occurrence of ISR has been investigated [8][9][10]. No studies have evaluated the effectiveness of the NLR value after (NLR after ), NLR change(NLR change ), defined as the NLR value before (NLR before ) and after (NLR after ) superficial femoral artery stenting (SFAS) intervention and NLR change ratio (NLR ratio ), defined as the ratio of NLR change to NLR before, in prediction of ISR in superficial femoral artery stents, which are at high risk for the occurrence of ISR.…”
Section: Introductionmentioning
confidence: 99%
“…This group reported activation of neutrophils and neutrophil-mediated oxidative burst in the inflammatory process of PCI-induced vessel injury and neointimal hyperplasia. Chang et al [26] recruited 180 patients and obtained venous blood samples one to three days before superficial femoral artery stent implantation. The neutrophil-lymphocyte ratio was computed using the absolute neutrophil count divided by the absolute lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…7 As shown in our study, the relationship between NLR and CRP was analyzed, and a positive correlation was found. 13 Diabetes and hyperlipidemia are known risk factors for atherosclerosis and restenosis. 14,15 Our study also found a significantly higher incidence of early ISR in diabetic patients than nondiabetic patients.…”
mentioning
confidence: 99%
“…14,15 Our study also found a significantly higher incidence of early ISR in diabetic patients than nondiabetic patients. 13 The proportion of diabetic patients in the high baseline NLR group (NLR ! 3.62) was significantly higher than that of the lower baseline NLR group (NLR < 3.62).…”
mentioning
confidence: 99%
See 1 more Smart Citation